Konsep Kebahagiaan al-Farabi dan Kontribusinya Terhadap Manusia Modern - Kurnia Sari Wiwaha; Dwi Setyo Arini; Resti Ananda Oktaviani (Journal of Comparative Study of Religions, 2022)
Al-Farabi is one of the Islamic philosophers who also focuses on the study of happiness. Although he is not the first scholar to talk about happiness, his thoughts have contributed to the study of Islamic thought. So that the authors are interested in studying al-Farabi's concept of happiness and analyzing the concept in order to answer the problems of modern humans, especially on the topic of finding happiness. To achieve this goal, the author uses library research by collecting primary sources such as books and scientific journals. Then, describe and analyze the data to find a correlation between al-Farabi's concept of happiness and the problems of mankind today. Thus, the author can provide input on how to take steps so that someone reaches happiness. According to al-Farabi happiness is a good that needs to be achieved. Every happiness is good, and every that is good must be happy. God himself created humans to be happy, so happiness needs to be made a life of goals. Al-Farabi explained that happiness can be achieved when the soul can be implemented optimally.